2020
DOI: 10.1038/s41467-020-19321-8
|View full text |Cite
|
Sign up to set email alerts
|

Divergent architecture of the heterotrimeric NatC complex explains N-terminal acetylation of cognate substrates

Abstract: The heterotrimeric NatC complex, comprising the catalytic Naa30 and the two auxiliary subunits Naa35 and Naa38, co-translationally acetylates the N-termini of numerous eukaryotic target proteins. Despite its unique subunit composition, its essential role for many aspects of cellular function and its suggested involvement in disease, structure and mechanism of NatC have remained unknown. Here, we present the crystal structure of the Saccharomyces cerevisiae NatC complex, which exhibits a strikingly different ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 82 publications
(151 reference statements)
11
35
0
Order By: Relevance
“…While Glu109 is positioned to function as a general base to deprotonate the α-amino group of the peptide substrate, Tyr121 is positioned to function as a general acid to re-protonate the CoA leaving group. This is consistent with the proposed roles of the analogous Glu118 and Tyr130 residues in Sc NatC (Grunwald et al, 2020) , as well as the conserved nature of these residues ( Figure 4a ). In addition, Naa30-Asn114 is highly conserved among all NATs (data not shown) and it was recently suggested to play a structural role in orienting the catalytic tyrosine residues ( Sp Naa30-Tyr135 and Tyr136) by ensuring the proper position of the active site helix (α4) for interaction with Ac-CoA (Deng et al, 2020b).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…While Glu109 is positioned to function as a general base to deprotonate the α-amino group of the peptide substrate, Tyr121 is positioned to function as a general acid to re-protonate the CoA leaving group. This is consistent with the proposed roles of the analogous Glu118 and Tyr130 residues in Sc NatC (Grunwald et al, 2020) , as well as the conserved nature of these residues ( Figure 4a ). In addition, Naa30-Asn114 is highly conserved among all NATs (data not shown) and it was recently suggested to play a structural role in orienting the catalytic tyrosine residues ( Sp Naa30-Tyr135 and Tyr136) by ensuring the proper position of the active site helix (α4) for interaction with Ac-CoA (Deng et al, 2020b).…”
Section: Resultssupporting
confidence: 89%
“…To investigate the catalytic roles of Naa38, we could readily purify both binary ( Sc Naa30 1-161 and Sc Naa35 19-733 ) and ternary Sc NatC complexes ( Sc Naa30 1-161 and Sc Naa35 19-733 , and Sc Naa38 1-70 ) from Saccharomyces cerevisiae to compare their activities. Consistent with the studies by Grunwald et al (Grunwald et al, 2020 ), evaluation of the activities of the binary and ternary Sc NatC complexes toward the canonical NatC substrate (MLRF peptide) revealed that the ternary complex showed robust activity, while the binary complex showed compromised activity ( Figure 1b ). Thus, it appears that Naa38 is required for optimal NatC activity in yeast.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations